Diabetic Striatopathy: Parenchymal Transcranial Sonography as a Supplement to Diagnosis at the Emergency Department - Massimiliano Godani; Giuseppe Lanza (Diagnostics, 2022)
Background: Diabetic striatopathy (DS) is a rare condition with a debated pathophysiology; a local metabolic dysfunction is the most likely hypothesis. We present a case of DS mimicking an acute stroke, outline a few uncommon/atypical features, and report for the first time the parenchymal transcranial sonography (pTCS) findings. Case Report: An 86-year-old man, treated for insulin-dependent diabetes, presented at an emergency department because of the occurrence of isolated choreo-athetotic movements in his left limbs with fluctuations in the location, frequency, and duration. The blood glucose level was 569 mg/dL. Both urgent and follow-up brain computed tomography (CT) were negative for recent lesions whereas pTCS revealed hyperechogenicity in the right lenticular nucleus. Subsequent magnetic resonance imaging (MRI) showed T1-weighted hyperintensity in the right putamen with negative diffusion-weighted imaging. The symptoms were responsive to glucose control and haloperidol administration, although they persisted during sleep. Conclusions: Unlike previously described cases characterized by hemichorea and/or hemiballism, our patient presented with a stroke-like onset of unilateral irregular choreo-athetotic movements. Notably, based on CT alone, it would not have been possible to distinguish DS from a stroke. In this scenario, the pTCS hyperechogenicity of the right lenticular nucleus helped to hypothesize a metabolic disorder, which was subsequently confirmed by MRI.